Behavior of redox-sensitive elements during weathering of granite in subtropical area using X-ray absorption fine structure spectroscopy. (1st June 2015) - Zhang, Zhuo-Jun; Liu, Cong-Qiang; Zhao, Zhi-Qi; Cui, Li-Feng; Liu, Wen-Jing; Liu, Tao-Ze; Liu, Bao-Jian; Fan, Bai-Ling
Highlights: A well-developed granite regolith in Jiangxi province, China was studied. XAFS was used to determine the speciation of Fe and Mn at main horizons of profile. Fe in saprolith is stabilized mainly in the state of Fe(III) at all the depths. Redox process impacts significantly on the mobility and redistribution of Mn, Ce, Co and V along the profile. Redox variation of profile is probably associated with SOM. Abstract: The variation in chemical compositions of regolith along a weathering profile developed on a granite substrate in Jiangxi province, in southern China, was investigated in this paper, with the aim to characterize the speciation of redox-sensitive elements and to evaluate their mobility and redistribution during chemical weathering. Mass balance calculations indicate titanium (Ti) is the most immobile element in this weathering profile. A new method, X-ray absorption fine structure (XAFS) spectroscopy, was used to determine the speciation of Fe and Mn along the profile. Fe K-edge X-ray absorption near edge structure (XANES) spectra show Fe in saprolith is stabilized mainly in the state of Fe(III), suggesting Fe is as immobile as conservative elements during granite weathering. Mn K-edge XANES spectra show Mn (III/IV) oxides are reduced to Mn(II) in surface soil, where soil organic matter (SOM) acts as an important reductant. Although Ce, Co and V were unable to be analysed by XAFS, their concentrations have significant correlations with that of Mn, indicating that the mobilization and redistribution of Ce, Co and V may also be governed by redox condition. All in all, the results suggest that redox process impacts significantly on the redistribution of Mn, Ce, Co and V along the profile. The successful application of XAFS in the study on migration of redox-sensitive elements during granite chemical weathering has provided valuable information for the understanding and evaluating the geochemical behavior of elements in the environment.